2012
DOI: 10.1016/j.socscimed.2012.02.045
|View full text |Cite
|
Sign up to set email alerts
|

Does school ethos explain the relationship between value-added education and teenage substance use? A cohort study

Abstract: Previous studies found lower substance use in schools achieving better examination and truancy results than expected, given their pupil populations (high value-added schools). This study examines whether these findings are replicated in West Scotland and whether school ethos indicators focussing on pupils' perceptions of schooling (environment, involvement, engagement and teacher–pupil relations) mediate the associations. Teenagers from forty-one schools (S2, aged 13, n = 2268; S4, aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 27 publications
2
19
0
1
Order By: Relevance
“…school completion officers, principals, and home school liaison) describing regular experiences with students visibly 'hungover ', 'dozy', 'stoned', 'unable to concentrate', or 'agitated' during classtime (Van Hout and Connor 2008). Such findings are also very much dependent on student -teacher relationships, with positive teacher and school bonding resulting in reduced rates of substance use and youth conflict, and positive levels of school satisfaction, classroom adjustment, and student motivation (Libbey 2004, Pianta and Stuhlman 2004, Gest et al 2005, Baker 2006, Doll and Cummings 2008, Davidson et al 2010, Markham et al 2012, Perra et al 2012. The mismatch between children and young people's development needs during transition or situation within second-level schooling may account for reduced academic motivation and performance, self-esteem, and potential for engagement in alcohol and drug use (Fenzel 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…school completion officers, principals, and home school liaison) describing regular experiences with students visibly 'hungover ', 'dozy', 'stoned', 'unable to concentrate', or 'agitated' during classtime (Van Hout and Connor 2008). Such findings are also very much dependent on student -teacher relationships, with positive teacher and school bonding resulting in reduced rates of substance use and youth conflict, and positive levels of school satisfaction, classroom adjustment, and student motivation (Libbey 2004, Pianta and Stuhlman 2004, Gest et al 2005, Baker 2006, Doll and Cummings 2008, Davidson et al 2010, Markham et al 2012, Perra et al 2012. The mismatch between children and young people's development needs during transition or situation within second-level schooling may account for reduced academic motivation and performance, self-esteem, and potential for engagement in alcohol and drug use (Fenzel 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The potential consideration of the school environment, where all educational staff are involved, reduces the potential biases incurred when teaching is restricted to one or two teachers delivering alcohol-and drug-related material and dependent on subjective translation of content (Markham and Aveyard 2003, Fletcher et al 2008, Paakkari et al 2010, Franklin et al 2012. In conjunction with this universaltype approach, teachers would also be advised to dedicate focus toward more vulnerable or 'at risk' students presenting with low school and teacher bonding, potential problematic substance use, and poor commitment to academic studies (Markham et al 2012).…”
mentioning
confidence: 99%
“…In all these studies except one (Tobler et al, 2011) this measure also included local deprivation so that these studies aimed to control for potential confounding by neighbourhood effects . With the exception of one study (Markham et al, 2012), the studies using this measure have reported consistent weak-to-moderate associations between value-added education and lower rates of smoking, drinking alcohol and drug use, even accounting for prior use in longitudinal studies (Markham et al, 2008, Tobler et al, 2011. Gross measures of educational attainment and truancy were not related to substance use.…”
Section: Quantitative Research On How the School Environment Influencmentioning
confidence: 88%
“…Another group of cross-sectional and longitudinal studies undertaken in the UK and USA has aimed to engage with this theory more directly by examining associations between 'valueadded education' and various measures of substance use (Aveyard et al, 2004, Bisset et al, 2007, Markham et al, 2008, Markham et al, 2012, Tobler et al, 2011. In these studies, value-added education was used as a proxy measure for the degree to which schools succeed in gaining students' commitments to the 'instructional' and 'regulatory' orders.…”
Section: Quantitative Research On How the School Environment Influencmentioning
confidence: 99%
“…The same goes for "positive social relationships" and "alternative activities to drug use". The former are contents of actions aimed at strengthening the positive social student-student, students-teachers, students-parents and teachers-parents networks (Jiménez et al 2014), which function as inhibitors of the likelihood of drug use by the students (the positive school ethos, Markham et al 2012).…”
Section: Discussionmentioning
confidence: 99%